The impact of information sharing on the performance of horizontal logistics collaboration: A simulation study in an agri-food supply chain. Issue 13 (2019) - Yuan, Yaxing; Viet, Nguyen; Behdani, Behzad
Abstract: In this paper, we study the value of horizontal logistics collaboration (HLC) for a case of Dutch horticultural supply chain. In order to deliver products on time, and hence, reach the desired service level, growers tend to carry out many trips in one day with low truck utilization. This situation can result in higher transportation cost, more pollution as well as low asset utilization. Collaborative logistics can be a potential strategy to cope with this situation. A simulation model is developed and the potential influencing factors the performance of HLC are studied. The results show that higher information sharing frequency can improve the performance by reducing the travel distance and improving service level and truck utilization. Moreover, the comparison of the performance with and without collaboration shows that that the growers with higher order frequency would potentially benefit more from an HLC setting © 2019 IFAC.